PENGARUH GAJI DAN KINERJA TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. LANCAR ABADI MEDAN - Grecia Yupastha; Syawaluddin Syawaluddin; Aidil Putra (STIE-PMCI, 2021)
Human resources are one of the company's main keys to developing well and supporting the company's success in achieving its goals. Human resources in question are: company employees. PT. Lancar Abadi Medan is a distributor company of Rice cooker Yong Ma's brand. In their daily activities, the company is faced with the problem of lack of employee discipline which can be seen in employees who are often late for work, neglect their duties and responsibilities, and not thorough in their work. This happens allegedly due to Salary and Performance factors from employees. The salary given is not in accordance with the job and also the position obtained is not according to ability, because it is not an employee's field. In addition, the performance of employees is also not high because the leader is unfair in providing targets to be achieved, and the division of tasks and responsibilities aren't according with the employee's position. The purpose of this study is to determine the effect of Salary and Performance on the work discipline of employees PT. Lancar Abadi Medan. The analytical method used is descriptive and quantitative analysis methods. The population in this study is 30 people who were employees of PT. Lancar Abadi Medan and also as a respondent. The methods of data collection is done by observation, interviews, documentation methods, questionnaires distribution, and literature studies. The Variable is measured by a Likert scale. The data analysis model is used to answer the hypothesis is multiple linear regression analysis.These results indicate that partially the salary does not significantly influence the work discipline of employees of PT. Lancar Abadi Medan, while Performance has a significant effect on the discipline of the employees of PT. Lancar Abadi Medan. And simultaneous, salary and performance influence the work discipline of employees of PT. Lancar Abadi Medan.Â Keywords: Salary, Performance, Work Disciplines